What Is in a Song? Constructions of Hegemonic Masculinity by Zimbabwean Football Fans - Ncube, Lyton; Chawana, Fiona (Routledge, 2021)
Raewyn Connell defines hegemonic masculinity as the most “honoured” way of being a man, and as such all men in patriarchal societies are expected to try to meet the standards of hegemonic masculinity (Connell and Messerschmitt 2005). It can be encountered in a variety of everyday contexts, one of which is sporting events. This article explores the authors’ ethnographic encounters with hegemonic masculinities amongst football fans in Zimbabwe, particularly in the songs they sing. Utilising Connell’s concept of hegemonic masculinity, the authors argue that Zimbabwean football fandom is entangled with hegemonic masculinities. The article demonstrates a simultaneously covert and subtle, but always complex, relationship between football fandom and masculinities, specifically hegemonic masculinity. The study’s major conclusion is that hegemonic masculinity is strongly discursive and occasionally occurs even in seemingly harmless mundane banter, such as stadium songs. Despite the sometimes jovial nature of these performances, there are power undercurrents involved.